Importance of angiotensinergic mechanisms for the pressor response to L-glutamate into the rostral ventrolateral medulla - Vieira, Alexandre Antonio; Colombari, Eduardo [UNESP]; De Luca, Laurival A.; Colombari, Debora S. A.; De Paula, Patricia M.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2010)
Pressor responses to L-glutamate into the rostroventrolateral medulla (RVLM) are reduced by lesions of the anteroventral third ventricle (AV3V) region, a main site related to central angiotensinergic pressor mechanisms. Therefore, similar to AV3V lesions, in the present study we investigated if the blockade of central angiotensinergic mechanisms with losartan or ZD 7155 might affect pressor responses to L-glutamate into the RVLM. Male Holtzman rats (280-320 g, n=4-8/group) with cannulas implanted into the RVLM and lateral ventricle (LV) were used. Injections of L-glutamate (5 nmol/100 nl) or angiotensin II (200 ng/100 nl) into the RVLM increased MAP (54 +/- 5 and 26 +/- 3 mm Hg, respectively). Losartan (100 mu g/1 mu l) or ZD 7155 (50 mu g/1 mu l) injected into the LV reduced the pressor responses to L-glutamate into the RVLM (22 +/- 5 and 26 +/- 7 mm Hg, respectively), without changing the pressor responses to angiotensin II into the RVLM. Losartan (10 mu g/100 mu l) or ZD 7155 (5 mu g/100 mu l) into the RVLM reduced the pressor response to L-glutamate (5 +/- 3 and 33 +/- 4 mm Hg, respectively) or angiotensin II (5 +/- 3 and 6 +/- 2 mm Hg, respectively) into the RVLM. Previous injection of angiotensin II (50 ng/100 nl) into the RVLM increased the pressor response to L-glutamate into the RVLM (from 44 +/- 5 to 68 +/- 7 mm Hg). The results suggest that angiotensinergic mechanisms directly in the RVLM and outside the RVLM (probably forebrain) are important for the pressor responses to L-glutamate into the RVLM. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Sympathetic; Rostral ventrolateral medulla; Hypothalamus; Angiotensin II; Blood pressure